Features of local etiological factors of periodontal disease in residents of high latitudes - I. D. Ushnitsky; O. S. Unusyan; Y. A. Akhremenko; K. V. Komzin; L. S. Unusyan; G. J. Badalyan (Эндодонтия Today)
Aim. The purpose of the article is to determine specific regional risk factors for periodontal diseases in residents of the North-East of Russia on a complex clinical and physiological research.Materials and methods. A clinical study of the biophysical properties and composition of oral fluid (salivation rate, pH, viscosity, microcrystallization type, lysozyme activity) in the adult population with inflammatory periodontal diseases were done at dental clinic of the Medical Institute of M.K.Ammosov North-Eastern Federal University, dental clinic "Valeon" and clinical and diagnostic laboratory "Scientific and Practical Center of Phthisiatry" (Yakutsk). A total of 1012 individuals aged 15-19 years old (n = 248) and 35-44 years old (n = 764) were examined. Oral hygiene in the age groups was assessed by the Oral Hygiene Index according to J.C. Green and J.R. Vermillion (1964). In addition, social and hygienic status was assessed according Yu. V.Chizhov's method (2005). Statistical processing was carried out using the SPSS software package, version 22. The research was performed in accordance with the principles and rules of evidence-based medicine.Results. The obtained results determine quantitative and qualitative changes in oral fluid properties. The presence of biological risk factors associated with changes in the composition and properties of the oral fluid, as well as a low sanitary level, which are associated with viscosity increase, salivation rate decrease, a predominance of II and III types of microcrystallization, acidic pH level, a decrease in the level of lysozyme activity, were revealed. The identified risk factors have an impact on the prevalence of periodontal disease in the people of the North and mostly determine their clinical course.Conclusion. The revealed biophysical features of oral fluid in the examined adolescents and adult population of the North-East of Russia are specific regional local risk factors for the development of periodontitis, which must be taken into account when improving the therapeutic and preventive measures of pathological processes of periodontal tissues.